Urticária e doenças sistêmicas - Criado,R. F. J. (1999)
Chronic urticaria and concurrent angioedema are disappoiting problems for both physicians and patients. The disease can result from multiple causes and probably does not have a single etiology. Several factors have been identified that appear to be important in the pathogenesis of individual cases, some drugs, food additives, physical factors and internal diseases. In some cases no pathogenesis are identified and those cases are classified as idiopathic. In recent years several articles has emphasized autoimmunity and infections due to Helicobacter pylori. Our article reviewed the etiology of chronic urticaria at current concepts.